Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Siswa Melalui Kombinasi Model PBL, TGT dan Pendekatan TPACK - Maysira Fatiya Nasution; Radiansyah (CV. ITTC INDONESIA, 2023)
Based on the observations, problems were found, namely activities, critical thinking skills and low student learning outcomes in PPKn learning. The solution to these problems is through the application of a combination of PBL, TGT, and TPACK Approach models. This study aims to describe teacher activities, student activities, and students' critical thinking skills and analyze student learning outcomes. The type of research used is Classroom Action Research (CAR) which is carried out for 4 meetings. The subjects of the study were 18 students of the VA class of SDN Melayu 6 Banjarmasin for the 2022/2023 academic year. Qualitative data includes teacher activities, activities and students' critical thinking skills obtained through observation sheets while quantitative data includes student learning outcomes obtained through written tests. The results showed an increase in teacher activity which scored 32, Student activity increased by 94%, Shiva's critical thinking skills increased by 89% and student learning outcomes increased by 94%. Based on the results of the study, it was concluded that the application of a combination of PBL, TGT, and TPACK Approach models can improve student activities, critical thinking skills and learning outcomes.